Chad : Staff Report for the 2013 Article IV Consultation and Assessment of Performance Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2014)
The staff report for the 2013 Article IV Consultation on Chad focuses on economic background and policy. The country continues to enjoy its longest period of domestic political stability since independence. Macroeconomic performance continued to be stable in 2013, with some deceleration in economic growth and inflation. Recently revised balance-of-payments data show that Chad has been running much larger external current account deficits. Chad's ability to tackle its developmental needs and poverty reduction objectives is seriously hampered by the projected oil revenue trajectory.